Si and SiGe Nanowire for Micro-Thermoelectric Generator: A Review of the Current State of the Art - Li, You; Wang, Guilei; Akbari-Saatlu, Mehdi; Procek, Marcin; Radamson, Henry H. (Frontiers in Materials, 2021)
In our environment, the large availability of wasted heat has motivated the search for methods to harvest heat. As a reliable way to supply energy, SiGe has been used for thermoelectric generators (TEGs) in space missions for decades. Recently, micro-thermoelectric generators (μTEG) have been shown to be a promising way to supply energy for the Internet of Things (IoT) by using daily waste heat. Combining the predominant CMOS compatibility with high electric conductivity and low thermal conductivity performance, Si nanowire and SiGe nanowire have been a candidate for μTEG. This review gives a comprehensive introduction of the Si, SiGe nanowires, and their possibility for μTEG. The basic thermoelectric principles, materials, structures, fabrication, measurements, and applications are discussed in depth.